2018
DOI: 10.1051/matecconf/201817402008
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight sintered aggregate as construction material in concrete structures

Abstract: Abstract. The paper presents the result of testing a new patented lightweight aggregates. The only solid material used to manufactured these aggregate is fly ash. Lightweight sintered aggregate is durable, lightweight and high-strength material. It is environmentally friendly material. It has chance to by future material in concrete use. The laboratory test shown that the concrete made from the this special lightweight sintered aggregate possesses low porosity, high strength and high durability potential. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Meanwhile, according to Grygo and Pranevich [ 48 ], the aggregate produced through the sintering process is lighter and has high strength performance. The sintering process is a popular application for mass manufacture of lightweight aggregates that does not require a long-term curing process [ 49 ].…”
Section: Manufacturing Of Lightweight Aggregatementioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, according to Grygo and Pranevich [ 48 ], the aggregate produced through the sintering process is lighter and has high strength performance. The sintering process is a popular application for mass manufacture of lightweight aggregates that does not require a long-term curing process [ 49 ].…”
Section: Manufacturing Of Lightweight Aggregatementioning
confidence: 99%
“…For instance, expanded perlite powder (EPP) was noted as being high in porosity, thus causing the water absorption to increase from 33% to 52% when the replacement of fly ash increased to 30% [ 53 ]. Meanwhile, when sintering is applied, increasing the sintering temperature was found to decrease water absorption of all aggregates due to the increment in the fusion of material, which led to less water surface permeability [ 48 ]. In the study conducted by Sun et al (2021) [ 65 ], it was found that the sintered aggregate made up of red mud and municipal solid waste incineration bottom ash with the temperature increased from 1010 °C to 1090 °C caused the porosity of the aggregate to increase and the water absorption to decrease significantly until 1070 °C.…”
Section: Physical and Mechanical Properties Of Lightweight Aggregatementioning
confidence: 99%
“…The use of secondary raw materials before natural ones is highly encouraged in the EU. Natural aggregate can be successfully replaced by waste materials [3][4][5]. An example of such material is sintered fly ash (SFA).…”
Section: Introductionmentioning
confidence: 99%